Different Grass Availabilities of Tropical Pasture on Performances and Carcasses of Lambs - N. da S. Heimbach; C. C. B. F. Ítavo; L. C. V. Ítavo; G. dos S. Difante; A. M. Dias; R. C. Brumatti; M. de N. B. Gomes; C. D. Baur; G. J. de Moraes; M. C. M. da Costa; N. D. Kozerski; E. S. Leal; A. L. C. Gurgel (Tropical Animal Science Journal, 2020)
This study aimed to identify the best green-leaf offerings of Urochloa brizantha cv. Marandu for pasture-finished lambs receiving protein-energy supplementation at the rate of 1.6% of their body weights (BW). The animals were assigned into four treatments, which consisted of varied green-leaf offerings, namely, 105, 90, 75, or 60 g of dry matter/kg of body weight (BW). Sixty-eight contemporary Texel × mixed-breed lambs with an average initial BW of 22.6 kg were used over two years of experiment. The experiment was set up in a completely randomized design, the data were evaluated by analysis of variance and the means were compared by Tukey’s test at the 0.05 significance level. There was no significant effect of year neither interaction of year with green-leaf offer. There were significant effects of leaf offer on dry matter intake (DMI) with behavior of positively linear (p<0.05). There were significant effects of green-leaf offer on final BW and average daily gain, and lambs receiving of 75 g/kg green-leaf offer showed the highest ADG (179 g/d). There were no significant differences in the carcass, meat, and primal cuts between the groups of lambs receiving different herbage offerings. There were significant effects of leaf offer on slaughter weight, hot carcass weight, and subcutaneous fat thickness. Lambs receiving of 75 g/kg leaf offer showed the highest SFT (5.8 mm). Slaughter weight and hot carcass weight averaged 41.52 kg and 20.07 kg, respectively. We recommend the treatment with leaves offer of 75 g/kg BW of Marandu pasture for the finishing of lambs supplemented at 1.6% of BW.